Battlefield assembly location algorithm based on single step weighted least squares - Yuchao ZHAO; Hongtuo YUAN; Ming SUN (Journal of Hebei University of Science and Technology, 2022)
Aiming at the problem that fast,high-precision and low-cost positioning is difficult to meet in typical non-cooperative areas,such as the battlefield assembly of airborne troops,a single-step weighted least squares algorithm was proposed based on the passive time difference positioning technology and the characteristics of actual station positioning and continuous positioning.According to the characteristics of the time difference location technology,the communication timestamp to each base station was recorded in the process of regional network distributed wireless communication,and the jet lag information was obtained.The two-step weighted least squares was implemented at first positioning,while the last positioning result was used as a prior information for the location input,simplifying the two-step weighted least squares to one-step weighted least squares.The results show that 6 to 8 stations are better location choices with the combination of station resource consumption and location accuracy for fixed station and random station.Compared with other algorithms,the location accuracy is better when the SNR is －10 to －20 dB.In special scenarios,the algorithm can achieve fast and accurate location,and has good performance under random station,which provides a reference for reducing the complexity of the algorithm in practical application.[HQ]